EFFECT OF PREOPERATIVE PREPARATION ON PATIENTS OUTCOME AMONG PATIENTS UNDERGOING SURGICAL OPERATIONS AT ALMIK NIMIR HOSPITAL – SUDAN - Al amine Ali, Eied Saber; Ahmed Abdallah, Higazi Mohammed (International Journal of Research -GRANTHAALAYAH, 2020)
Preoperative preparations of the patients physically and psychologically are the cornerstone of the good outcomes. This prospective quasi-experimental hospital-based study was conducted in Sudan, Shendi city at Elmek Nimer university hospital to evaluate the impact of preoperative preparation on patients outcome among patients undergoing general surgery. In the period of June 2016 to May 2019. The study was included a hundred patients undergoing general elective surgery, data were collected by interviewing questionnaire, anxiety scale, pain assessment tool, postoperative parameter, and patients satisfaction tool, data were collected in two phases (pre& postoperative). The data were analyzed by the computer software program (SPPS) version 20. The results showed that more than two third (79.4%) of the patient had poor knowledge about the importance of preoperative preparations, but improve after implemented program and this was reflected on patient behavior and outcome in the postoperative phase. (70%) had reported no anxiety to mild in the postoperative phase. in regard of postoperative pain, majority of patients (70%) experienced moderate to severe level of pain in the first 4 hours, this level of pain reduce to mild to no pain level in (82%) of patients in next 12hours. Most of the patients had full to good satisfaction regarding preparations and outcome. The study support and justifies the effectiveness of the preoperative preparations on patient outcomes. The study recommended surgical nurses have to provide proper explanation and teaching for elective surgical patients to be adherence with the care plan to promote good surgical outcome.